Image-guided Retrieval of Foreign Body in the Abdomen - A Case Report - Pandya, Jayashri Sanjay; Waghmare, Sudatta; Unnikrishnan, Arjun; Varma, Ravi (Indian Journal of Case Reports, 2018)
The presence of retained surgical blade as a foreign body is uncommon and poses significant patient safety challenge issues. Most common etiologies for the presence of such foreign bodies are accidental, traumatic, or iatrogenic. Here, we report a successful management of the case with a rare foreign body in the abdomen, that is, surgical blade accidentally left during pigtail procedure of the liver abscess. Most of the iatrogenic injuries are preventable. In our case, a misfit of a blade in the handle might have been responsible for the complication. The use of radiological guidance for localization and removal of the foreign bodies embedded in the soft tissues is well established. With imaging guidance retrieval of a foreign body in the abdomen, laparotomy was prevented and facilitated early recovery.